Lead-free sulfide quantum dot glass and application
By synthesizing lead-free sulfide quantum dots in situ in glass, and induced CuInS2 or CuGaS2 generation by using ZnS, the problems of poor thermal stability and toxic heavy metals in the prior art are solved, and efficient and environmentally friendly photoluminescence and adjustable display are achieved. Color capability, suitable for lighting and backlight display.
Patent Information
- Application Number
- CN202411610161.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-03
AI Technical Summary
The existing I-II-VI quantum dot materials are damaged at high temperatures, their optical properties change, their thermal stability is poor, and they contain toxic heavy metal elements Pb and Cd, which is difficult to widely use in light-emitting devices, and their color rendering capabilities are traditional light sources. Insufficient, high production costs.
Lead-free sulfide quantum dot glass, including Cu2S and Group III compounds, induced CuInS2 or CuGaS2 quantum dot generation through ZnS as the nucleation center, and promoted through Na2S and ZnS to improve luminescence efficiency and thermal stability, 450-510℃ The heat treatment can adjust the luminescence intensity and wavelength, and use lead-free sulfide quantum dot glass to cooperate with the ultraviolet luminescence chip as a white light source.
It realizes the high thermal stability and environmental protection of lead-free sulfide quantum dot glass, with broadband emission capabilities in the range of 290nm-365nm, adjustable luminescence center, environmental tolerance temperature up to 240℃, and multiple thermal cycle tests without permanent damage. Reduced production costs.
Smart Images

Figure CN119241069A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of optical technology, and specifically relates to lead-free sulfide quantum dot glass and applications thereof. Background Art
[0002] Quantum dot materials with PbS, GdS, and PbSe as luminescent centers play an important role in daily life and industrial manufacturing due to their high luminescence efficiency and adjustable luminescence wavelength. However, during their production and recycling, the heavy metal elements Pb and Cd in them are easy to pollute the site, water bodies, and soil, causing poisoning of animals and plants. The luminescence band of group I-III-VI quantum dots is similar to and adjustable to that of quantum dots containing Pb and Cd. At the same time, they do not contain toxic heavy metal elements such as Pb and Cd, and have the potential to be used as new quantum dot luminescent materials. However, the microstructure of group I-III-VI quantum dots is destroyed and the optical properties change at 200°C. Therefore, the poor thermal stability makes it difficult to be directly used in light-emitting devices. Moreover, since sulfur elements such as S and Se exist in the form of anions in quantum dot materials, organic encapsulation or humid environment can easily cause them to be sulfonated, thereby destroying the quantum dot structure. Therefore, this type of quantum dot material has not yet been widely used in the field of photoluminescence. In addition, natural light is full-band light, while traditional lighting / display uses light modulated by the three primary colors of red, green, and blue, which makes the color rendering ability of traditional artificial light sources lacking compared to natural light. In order to produce light sources with a full visible light spectrum range, existing technologies need to use more types of phosphors, which undoubtedly increases production costs. Therefore, it is crucial to explore a material with adjustable luminescent center and luminous intensity. Summary of the invention
[0003] In view of the above-mentioned shortcomings of the prior art, the present invention provides a lead-free sulfide quantum dot glass and its application.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] A lead-free sulfide quantum dot glass comprises raw material A, Cu2S and a group III compound, wherein the molar ratio of raw material A, Cu2S and group III compound is 100: 0.01-0.1: 0.01-0.5; the raw material A comprises raw materials with the following molar percentages: 30%-40% SiO2, B% Al2O3, C% B2O3, 6%-16% ZnO, 25% Na2CO3, x% ZnS, (4-x)% Na2S, 1≤x≤4, B+C=25%; the group III compound is In2O3 or Ga2O3;
[0006] The preparation method of the lead-free sulfide quantum dot glass comprises the following steps:
[0007] (1) mixing and grinding lead-free sulfide quantum dot glass raw materials, then melting them, and then pouring them into a preheated mold and cooling them;
[0008] (2) The cooled and solidified glass is subjected to annealing treatment and heat treatment in sequence to obtain lead-free sulfide quantum dot glass.
[0009] The present invention uses ZnS as a nucleation center to induce the generation of CuInS2 or CuGaS2 quantum dots, and ZnS acts as a transition layer between the CuInS2 or CuGaS2 quantum dots and the glass matrix, thereby reducing the surface defects of the CuInS2 or CuGaS2 quantum dots and improving the luminescence efficiency and luminescence thermal stability of the lead-free sulfide quantum dot glass. In addition, the present invention promotes the generation of CuInS2 or CuGaS2 quantum dots through Na2S and ZnS, thereby improving the luminescence efficiency and luminescence thermal stability of the lead-free sulfide quantum dot glass, and the present invention is heat-treated at 450-510°C, so that the luminescence intensity and luminescence center wavelength of the lead-free sulfide quantum dot glass are adjustable, and as the heat treatment temperature increases, the luminescence center wavelength red-shifts, and the luminescence intensity first increases and then decreases.
[0010] As a preferred embodiment of the present invention, the melting temperature is 1250-1350° C., and the melting time is 25-35 minutes.
[0011] As a preferred embodiment of the present invention, the preheating temperature of the mold is 300-350°C.
[0012] As a preferred embodiment of the present invention, the mold is a copper mold.
[0013] As a preferred embodiment of the present invention, the annealing temperature is 300-350° C., and the annealing time is 2-5 hours.
[0014] As a preferred embodiment of the present invention, the heat treatment temperature is 0 to 510° C., and the treatment time is 5 to 15 hours.
[0015] More preferably, the heat treatment temperature is 450-510° C., and the treatment time is 5-15 hours.
[0016] As a preferred embodiment of the present invention, the application of the lead-free sulfide quantum dot glass in lighting and backlight display specifically includes: cutting and polishing the lead-free sulfide quantum dot glass, making it into a suitable size, and then compounding it with an ultraviolet light-emitting chip to use it as a white light source.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention does not use toxic heavy metal elements such as Pb and Cd, and is environmentally friendly. The present invention synthesizes lead-free sulfide quantum dots in situ in glass, and the prepared glass matrix increases the thermal stability of the quantum dots, and the environmental tolerance temperature is as high as 240°C. Under the excitation of a wide-band ultraviolet light source of 290nm-365nm, the lead-free sulfide quantum dot glass exhibits a broadband emission capability with a half-width of 175nm, which is adjustable around 400nm-600nm. The photoluminescence of the prepared lead-free sulfide quantum dot glass decays with the increase of the working environment temperature, but no permanent damage is shown in multiple thermal cycle tests. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 1 and 2. The XRD diagrams of the lead-free sulfide quantum dot glass prepared in Example 3 and Comparative Example 4 are shown in FIG. 1 , wherein the lead-free sulfide quantum dot glass before heat treatment is the lead-free sulfide quantum dot glass prepared in Comparative Example 4, and the lead-free sulfide quantum dot glass after heat treatment is the lead-free sulfide quantum dot glass prepared in Example 3.
[0019] Figure 2 This is the TEM image of the lead-free sulfide quantum dot glass prepared in Example 3.
[0020] Figure 3 Spectra of the lead-free sulfide quantum dot glasses prepared in Examples 1-3 and Comparative Examples 4-5 under 365nm ultraviolet light.
[0021] Figure 4 The photoluminescence CIE coordinate diagram of the lead-free sulfide quantum dot glass prepared in Examples 1-3, Comparative Example 5 and Comparative Example 4.
[0022] Figure 5 This is a temperature-dependent spectrum diagram of the lead-free sulfide quantum dot glass prepared in Example 3 at 30-240°C.
[0023] Figure 6 This is a graph showing the cycling performance of the lead-free sulfide quantum dot glass prepared in Example 3 at 30-240°C. DETAILED DESCRIPTION
[0024] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0025] Example 1
[0026] A sulfide quantum dot glass comprises a raw material A, Cu2S and a group III compound, wherein the molar ratio of the raw material A, Cu2S and In2O3 is 100:0.01:0.1.
[0027] The raw material A includes the following raw materials in molar percentage: 40% SiO2, 25% B2O3, 6% ZnO, 25% Na2CO3, 1.5% ZnS, and 2.5% Na2S.
[0028] A method for preparing quantum dot glass comprises the following steps:
[0029] (1) Grind 10 g of glass raw material for 10 minutes to mix well. Then transfer the ground material into an alumina crucible. Then put the crucible containing the material into a chamber muffle furnace, set the temperature to 1300°C, and melt for 30 minutes.
[0030] (2) After the glass melt is melted at high temperature, it is taken out from the box-type muffle furnace and poured into a copper plate mold preheated to 280°C, so that it can be quickly cooled and formed. It is then immediately placed in a small muffle furnace at 300°C for annealing for 2 hours to eliminate thermal stress.
[0031] (3) The annealed glass was placed in a small muffle furnace and kept at 470°C for 10 hours.
[0032] Example 2
[0033] The raw materials of the sulfide quantum dot glass in this embodiment are the same as those in Embodiment 1.
[0034] The only difference between the method for preparing a sulfide quantum dot glass in this embodiment and that in embodiment 1 is that the temperature in step (3) is kept at 490° C. for 10 hours.
[0035] Example 3
[0036] The raw materials of the sulfide quantum dot glass in this embodiment are the same as those in Embodiment 1.
[0037] The only difference between the method for preparing a sulfide quantum dot glass in this embodiment and that in embodiment 1 is that the temperature in step (3) is kept at 510° C. for 10 hours.
[0038] Example 4
[0039] A sulfide quantum dot glass comprises a raw material A, Cu2S and a group III compound, wherein the molar ratio of the raw material A, Cu2S and In2O3 is 100:0.05:0.2.
[0040] The A raw material includes the following raw materials in molar percentage: 35% SiO2, 15% B2O3, 10% Al2O3, 11% ZnO, 25% Na2CO3, 1.5% ZnS, and 2.5% Na2S.
[0041] The method for preparing the quantum dot glass comprises the following steps:
[0042] (1) Grind 10 g of glass raw material for 10 minutes to mix well. Then transfer the ground material into an alumina crucible. Then put the crucible containing the material into a chamber muffle furnace, set the temperature to 1350°C, and melt for 25 minutes.
[0043] (2) After the glass melt is melted at high temperature, it is taken out from the box-type muffle furnace and poured into a copper plate mold preheated to 280°C, so that it can be quickly cooled and formed. It is then immediately placed in a small muffle furnace at 300°C for annealing for 2 hours to eliminate thermal stress.
[0044] (3) The annealed glass was placed in a small muffle furnace and kept at 450°C for 15 hours.
[0045] Example 5
[0046] A sulfide quantum dot glass comprises a raw material A, Cu2S and a group III compound, wherein the molar ratio of the raw material A, Cu2S and Ga2O3 is 100:0.1:0.5.
[0047] The A raw material includes the following raw materials in molar percentage: 30% SiO2, 15% B2O3, 10% Al2O3, 16% ZnO, 25% Na2CO3, 1.5% ZnS, and 2.5% Na2S.
[0048] The method for preparing the quantum dot glass comprises the following steps:
[0049] (1) Grind 10 g of glass raw material for 10 minutes to mix well. Then transfer the ground material into an alumina crucible. Then put the crucible containing the material into a chamber muffle furnace, set the temperature to 1250°C, and melt for 35 minutes.
[0050] (2) After the glass melt is melted at high temperature, it is taken out from the box-type muffle furnace and poured into a copper plate mold preheated to 350°C, so that it is quickly cooled and formed, and then immediately placed in a small muffle furnace at 350°C for annealing for 5 hours to eliminate thermal stress.
[0051] (3) The annealed glass was placed in a small muffle furnace and kept at 500°C for 5 hours.
[0052] Comparative Example 1
[0053] CuInS2 quantum dot synthesis method: 0.125mmol of copper iodide, 0.5mmol of indium acetate and 5mL of 1-dodecyl mercaptan were placed in a 50mL three-necked flask and heated at 100℃ for 1 hour while degassing. Then the precursor was heated to 230℃ under argon flow, and the temperature was maintained and samples were taken every 1min to obtain CuInS2 quantum dots of different sizes.
[0054] The prepared CuInS2 quantum dots decomposed at 240°C and experienced irreversible luminescence degradation after working at 85°C for one hour, indicating that the thermal stability of CuInS2 quantum dots was poor.
[0055] Comparative Example 2
[0056] A sulfide quantum dot glass comprises a raw material A, Cu2S and a group III compound, wherein the molar ratio of the raw material A, Cu2S and In2O3 is 100:0.01:0.1.
[0057] The raw material A includes the following raw materials in molar percentage: 40% SiO2, 25% B2O3, 6% ZnO, 25% Na2CO3, and 4% Na2S.
[0058] A method for preparing quantum dot glass comprises the following steps:
[0059] (1) Grind 10 g of glass raw material for 10 minutes to mix well. Then transfer the ground material into an alumina crucible. Then put the crucible containing the material into a chamber muffle furnace, set the temperature to 1300°C, and melt for 30 minutes.
[0060] (2) After the glass melt is melted at high temperature, it is taken out from the box-type muffle furnace and poured into a copper plate mold preheated to 280°C, so that it can be quickly cooled and formed. It is then immediately placed in a small muffle furnace at 300°C for annealing for 2 hours to eliminate thermal stress.
[0061] (3) The annealed glass was placed in a small muffle furnace and kept at 450°C, 470°C, 490°C, 510°C, and 520°C for 10 hours respectively.
[0062] Comparative Example 3
[0063] A sulfide quantum dot glass comprises a raw material A, Cu2S and a group III compound, wherein the molar ratio of the raw material A, Cu2S and In2O3 is 100:0.01:0.1.
[0064] The raw material A includes the following raw materials in molar percentage: 40% SiO2, 25% B2O3, 6% ZnO, 25% Na2CO3, and 4% ZnS.
[0065] A method for preparing quantum dot glass comprises the following steps:
[0066] (1) Grind 10 g of glass raw material for 10 minutes to mix well. Then transfer the ground material into an alumina crucible. Then put the crucible containing the material into a chamber muffle furnace, set the temperature to 1300°C, and melt for 30 minutes.
[0067] (2) After the glass melt is melted at high temperature, it is taken out from the box-type muffle furnace and poured into a copper plate mold preheated to 280°C, so that it can be quickly cooled and formed. It is then immediately placed in a small muffle furnace at 300°C for annealing for 2 hours to eliminate thermal stress.
[0068] (3) The annealed glass was placed in a small muffle furnace and kept at 450°C, 470°C, 490°C, 510°C, and 520°C for 10 hours respectively.
[0069] Comparative Example 4
[0070] The raw materials of the sulfide quantum dot glass in this comparative example are the same as those in Example 1.
[0071] The only difference between the method for preparing a sulfide quantum dot glass in this comparative example and that in Example 1 is that no heat treatment is performed in step (3).
[0072] Comparative Example 5
[0073] The raw materials of the sulfide quantum dot glass in this comparative example are the same as those in Example 1.
[0074] The only difference between the preparation method of a sulfide quantum dot glass in this comparative example and that in Example 1 is that the temperature in step (3) is kept at 520° C. for 10 hours.
[0075] according to Figure 1 , Comparative Example 4: The sample without heat treatment is as follows Figure 1 XRD shows that the glass-like bun peaks are obvious after heat treatment. This indicates that sulfide quantum dots are successfully precipitated in the glass matrix after heat treatment. It is found that the main diffraction peaks of lead-free sulfide quantum dot glass are similar to the PDF#47-1372 card of CuInS2, but the peaks are shifted to the large angle direction, indicating that Cu in quantum dots + 、In 3+ With Zn in glass 2+ Mutual migration and doping form ZnS and CuInS2 composite sulfide solid solution.
[0076] according to Figure 2 The (121) interplanar spacing of the microcrystals formed in the glass sample described in Example 3 is 0.24 nm, and the (112) interplanar spacing is 0.32 nm, which is consistent with the interplanar spacing of CuInS2 in the PDF#47-1372 card, and the size of the microcrystals is less than 10 nm.
[0077] according to Figure 3It can be seen that under 365nm ultraviolet light irradiation, the peak value of the luminescent wavelength of the samples prepared in Examples 1-3 and Comparative Examples 4-5 and treated at different temperatures red-shifts with the increase of the heat treatment temperature, and the luminescent intensity of the samples treated at different temperatures first increases and then decreases with the increase of the heat treatment temperature, and the lead-free sulfide quantum dot glass exhibits a broadband emission capability with a half-width of 175nm and adjustable around 400nm-600nm. And at room temperature, under 365nm ultraviolet light irradiation, the luminescent intensity of Example 4 is similar to that of Example 1, the luminescent intensity of Example 5 is similar to that of Example 3, the luminescent intensity of Comparative Example 2 is similar to that of Example 3, and the luminescent intensity of Comparative Example 3 is similar to that of Comparative Example 4.
[0078] according to Figure 4 The CIE color coordinates corresponding to the luminescence wavelength of the sulfide quantum dot glass prepared in Examples 1-3 and Comparative Example 5 under 365nm ultraviolet light excitation are calculated, proving that the luminescence of the sulfide quantum dot glass prepared in the present invention can achieve an adjustable color temperature of 10000K to 3000K, and has application potential as a high color rendering light source.
[0079] according to Figure 5, the sulfide quantum dot glass prepared in Example 3 was crushed and ground into powder. It was heated from 30°C to 240°C, and tested once every 30°C. The quantum dot glass can be excited by a 280-370nm light source under 295nm ultraviolet light excitation. The emission wavelength was slightly offset under different light sources, but the effect was not significant. The luminescence intensity of the sample decayed with increasing temperature. The sulfide quantum dot glass prepared in Example 3 has an environmental tolerance temperature of up to 240°C. Its luminescence intensity decayed to 50% at 300°C, but no permanent damage was caused. The luminescence intensity of the samples of Examples 1-5 and Comparative Examples 2-5 decayed with increasing temperature, and the high temperature resistance to the environment can reach 240°C. Among them, Examples 1-3 and Comparative Examples 4-5 show that the sulfide quantum dot glass has a broadband emission with an adjustable center of 400nm-600nm and a half-height width of 175nm within the heat treatment temperature of 0-520°C, but the luminescence intensity is weak when heat treated at 520°C. Examples 4 and 5 also have the performance of broadband emission with an adjustable center of 400nm-600nm and a half-width of 175nm after heat treatment at a temperature of 0-510°C. The sample of Comparative Example 2 prepared at a heat treatment temperature of 510-520°C shows the performance of adjustable luminescence center and luminescence intensity under 365nm ultraviolet light irradiation. The adjustable condition range (510-520°C heat treatment temperature) is too narrow and too sensitive to the heat treatment temperature, that is, a small change in the heat treatment temperature will have a greater impact on its luminescence center. Considering that there are always small temperature errors that are difficult to avoid during the heat treatment process, the sample of Comparative Example 2 is not suitable as an object of luminescence regulation. The sample of Comparative Example 3 prepared at a heat treatment temperature of 450-520°C has no change in luminescence intensity, luminescence center and luminescence half-width under 365nm ultraviolet light irradiation. The sample of Comparative Example 3 does not have the performance of adjustable luminescence center and luminescence intensity.
[0080] according to Figure 6 , the sulfide quantum dot glass prepared in Example 3 was crushed and ground into powder, and then the sample was heated from 60°C to 240°C and kept warm for 20 minutes before testing its luminous intensity. When the temperature of the sample dropped to 60°C, its luminous intensity was tested again, and the test was repeated. It can be seen that the luminous performance of the sample at 240°C in the initial state was 66.1% of that at 60°C. After 9 cycles, the luminous performance of the sample at 60°C was 97.6% of that in the initial state, and the luminous performance of the sample at 240°C was 66.1% of that in the initial state. The high temperature performance of the sample was not attenuated, and the sample proved that the material had excellent thermal stability.
[0081] The materials prepared in Examples 1-2, Examples 4-5 and Comparative Examples 2-5 were cycled 9 times at 60°C and 240°C. The luminescence performance of the samples at 240°C was about 60% of the initial state, and the high temperature performance of the samples did not decay. The samples proved that the materials had excellent thermal stability. However, the luminescence intensity of Comparative Examples 3, 4 and 5 at 240°C was weak and the luminescence was not obvious.
[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A lead-free sulfide quantum dot glass, characterized in that: The invention comprises raw material A, Cu2S and a group III compound, wherein the molar ratio of raw material A, Cu2S and group III compound is 100: 0.01-0.1: 0.01-0.5; the raw material A comprises raw materials with the following molar percentages: 30%-40% SiO2, B% Al2O3, C% B2O3, 6%-16% ZnO, 25% Na2CO3, x% ZnS, (4-x)% Na2S, 1≤x≤4, B+C=25%; the group III compound is In2O3 or Ga2O3; The method for preparing the lead-free sulfide quantum dot glass is characterized by comprising the following steps: (1) mixing and grinding lead-free sulfide quantum dot glass raw materials, then melting them, and then pouring them into a preheated mold and cooling them; (2) The cooled and solidified glass is subjected to annealing treatment and heat treatment in sequence to obtain lead-free sulfide quantum dot glass.
2. The lead-free sulfide quantum dot glass according to claim 1, characterized in that: The melting temperature is 1250-1350° C., and the melting time is 25-35 minutes.
3. The lead-free sulfide quantum dot glass according to claim 1, characterized in that: The preheating temperature of the mold is 280-350°C.
4. The lead-free sulfide quantum dot glass according to claim 1, characterized in that: The annealing temperature is 300-350° C., and the annealing time is 2-5 hours.
5. The lead-free sulfide quantum dot glass according to claim 1, characterized in that: The heat treatment temperature is 450-510° C., and the treatment time is 5-15 hours.
6. Application of the lead-free sulfide quantum dot glass according to any one of claims 1 to 5 in lighting and backlight display.
